Apa yang mempengaruhi Kepercayaan Muzakki Terhadap Organisasi Pengelola Zakat: Sebuah Kajian Systematic literature review - Pasya, Dien Annida Aslamah; Handoko, Luqman Hakim (Journal of Islamic Philanthropy and Disaster (JOIPAD), 2025)
This study aims to examine the current state of the literature regarding the factors that influence muzakki's trust in Zakat Management Organizations. The type of data used is secondary data taken from Google Scholar using PoP software. The method used is descriptive qualitative with Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) analysis. The research results show that 2021 is the year with the most articles published, with 7 scientific articles, and BAZNAS is the place where the most case studies were conducted. Muzakki’s trust can be measured in four indicators: integrity, competence, consistency, and benevolence. The factors that determine muzakki's trust include four variables: accountability, transparency, amil literacy, and service quality. Based on these indicators, finally, this research yields a conceptual model of determining muzakki's trust in OPZ.